The adequacy of consumer protection act 1999 in protecting consumers' rights in Malaysia over misleading and deceptive conduct / Asma’i Abdul Rauf … [et al.] - Abdul Rauf, Asma'i; Mohd Rowardi, Nadira Izati; Anuar, Nur Afida; Harun, Nurul Husna; Ramli, Nurul Syahida (Faculty of Law, 2010)
This research is a critical analysis on the adequacy of Malaysian Consumer Protection Act 1999 (CPA 1999) in governing consumers' protection. CPA 1999 was enforced on October 1999 under the Ministry of Domestic Trade, Cooperation and Consumerism in order to provide a greater protection to the consumers. Under the Act, the rights granted as the consumers cannot be taken away from consumers notwithstanding conditions in any agreement that they have signed. However, after more than 10 years of enforcement, consumers' rights are still being abused either by the traders or the consumers themselves. This led to a question where is the significant and effectiveness of the CPA 1999 of consumers' rights which are still fail to be upheld? It might be some loopholes of the said Act which make it inefficient. Thus, this study was conducted in order to examine the adequacy of the CPA 1999 in protecting consumers' rights over misleading and deceptive conduct in Malaysia.